What Drives Spatial Clusters of Entrepreneurship in China? Evidence from Economic Census Data - Liang Zheng; Zhong Zhao (Institute of Labor Economics (IZA), 2017)
Since Chinese government initiated economic reform in the late 1970s, entrepreneurship and private sectors have emerged gradually and played an increasingly important role in promoting economic growth. However, entrepreneurship is distributed unevenly in China. Using micro data from 2008 economic census and 2005 population census, this paper explains spatial clusters of entrepreneurship for both manufacturing and services. For both sectors, entrepreneurship (measured by new private firms) tends to emerge in places with more relevant upstream and downstream firms. Moreover, Chinitz's (1961) theories are also supported for manufacturing: small upstream and downstream firms seem to be more important for manufacturing entrepreneurship. For both sectors, entrepreneurship is positively related to city size, the share of young adults and the elderly population, and foreign direct investment. More migrants are also found to promote service entrepreneurship. Our paper is the first to consider both manufacturing and service entrepreneurship in China and should be of interest to both local and national policymakers who plan to encourage entrepreneurship.
Keywords: L26; L60; L80; R10; R12; 330; new firm formation; entrepreneurship; Marshallian effect; Chinitz effect; China